Effect of Beam Span Variation on Partially Prestressed and Reinforced Concrete Buildings: A Comparative Study - Acharya, Pratima; Adhikari, Badri; Baral, Sanjay (Technical Journal, 2025)
Partially prestressed concrete (PPC) buildings are gaining popularity in modern engineering world due to their improved strength and durability compared to the reinforced concrete (RC) building. PPC structure combine both reinforcement and prestressing elements, integrating the advantages of RC and prestressed structures. However, research on PPC buildings remains limited in Nepal, despite rapid infrastructure and urbanization growth. This study focus on the comparing the performance of PPC and RC buildings by analyzing six models each with varying beam spans ranging from 6m to 16m in an eight storey building structure using SAP2000 v20 tool. The primary parameters analyzed include maximum bending moment, shear force, stress distribution, deflection and span to depth ratio. The analysis of the PPC buildings showed lower bending moments, lower bending stresses and smaller beam sections compare to RC buildings. This leads to a higher span to depth ratio, for PPC building increasing from 16.67 (for a 6m beam span) to 35.55 (for a 16m beam span) and for RC buildings from 15 (for a 6m span) to 20 (for a 16m beam span) while staying within prescribed limits. Additionally, prestressing enhances material efficiency, making PPC buildings more suitable for longer beam spans. This study highlights the advantages of PPC structures in optimizing structural performance and provides useful insights for engineers and architects in designing efficient and resilient buildings.